(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This research paper investigates the stress load experienced by nurse managers in their daily activities amidst the COVID-19 pandemic. The study aims to analyze the unique challenges faced by nurse managers during this unprecedented time, focusing on the increased workload, emotional strain, and organizational pressures they encounter. By utilizing both quantitative and qualitative research methods, this paper explores the impact of pandemic-related stress on the well-being and performance of nurse managers, as well as strategies that can be implemented to support their mental health and job satisfaction. The findings of this study shed light on the importance of addressing stress management in healthcare leadership roles, particularly during crises such as the COVID-19 pandemic.